Parcellation‐based anatomic modeling of the default mode network. Issue 2 (18th December 2020) - Sandhu, Zainab; Tanglay, Onur; Young, Isabella M.; Briggs, Robert G.; Bai, Michael Y.; Larsen, Micah L.; Conner, Andrew K.; Dhanaraj, Vukshitha; Lin, Yueh‐Hsin; Hormovas, Jorge; Fonseka, Rannulu Dineth; Glenn, Chad A.; et al.
Abstract: Background: The default mode network (DMN) is an important mediator of passive states of mind. Multiple cortical areas, such as the anterior cingulate cortex, posterior cingulate cortex, and lateral parietal lobe, have been linked in this processing, though knowledge of network connectivity had limited tractographic specificity. Methods: Using resting‐state fMRI studies related to the DMN, we generated an activation likelihood estimation (ALE). We built a tractographical model of this network based on the cortical parcellation scheme previously published under the Human Connectome Project. DSI‐based fiber tractography was performed to determine the structural connections between cortical parcellations comprising the network. Results: Seventeen cortical regions were found to be part of the DMN: 10r, 31a, 31pd, 31pv, a24, d23ab, IP1, p32, POS1, POS2, RSC, PFm, PGi, PGs, s32, TPOJ3, and v23ab. These regions showed consistent interconnections between adjacent parcellations, and the cingulum was found to connect the anterior and posterior cingulate clusters within the network. Conclusions: We present a preliminary anatomic model of the default mode network. Further studies may refine this model with the ultimate goal of clinical application. Abstract : Using attentional task‐based fMRI studies to generate an activation likelihood estimation (ALE), we built a tractographical model of this network. Seventeen cortical regions were found to be part of the DMN: 10r, 31a, 31pd, 31pv, a24, d23ab, IP1, p32, POS1, POS2, RSC, PFm, PGi, PGs, s32, TPOJ3, and v23ab. These regions showed consistent interconnections between adjacent parcellations, and the cingulum was found to connect the anterior and posterior cingulate clusters within the network.